Ginger (Zingiber officinale Rosc.) in South Eastern Nigeria. II. The field response of the uncoated ginger Yatsun-biri for rapid seed ginger production - OKWUOWULU, P A (Journal of Spices and Aromatic Crops, 1994)
Sett weights (9, 7, 5 and 3 g) were assessed for rapid seed ginger (Zingiber officinale) multiplication at varying intra-rows (20, 15 and 10 em) at two locations in South Eastern Nigeria. Establishment counts increased with larger setts but sowing off-sized setts ( 3 g) offers potential for rapid seed harvest and multiplication ratio. Close planting (10 cm within-row spacing) and larger setts produced significantly higher yields of rhizomes but not seed harvest multiplication ratio.